PEMETAAN PERSEBARAN RAFFLESIA DI KAWASAN CAGAR ALAM MANINJAU KABUPATEN AGAM - Wely Yelvia Sartika; Iswandi Umar (JURNAL BUANA, 2022)
This research was carried out in the Maninjau Nature Reserve, Agam Regency to determine the distribution of Rafflesia, map habitat suitability and determine physical factors the most influential on the habitat Rafflesia. In analyzing the distribution and suitability of the habitat Rafflesia using the method Species Distribution Modeling (SDM) with Maximum Entropy (MaxEnt) analysis of the habitat indicators Rafflesia including height, slope, land cover, soil type and distance from the river. Based on the results of the study found 13 growing points of Rafflesia as many as 35 individuals Rafflesia consisting of 1 individual in the blooming condition, 10 individuals in the post-bloom condition, and 16 individuals in the knob condition. The results of Maxent's modeling on the distribution and characteristics of the habitat Rafflesia in the Maninjau Nature Reserve are as follows: found at an altitude between 950-1100 mdpl which is in forest land cover type, is on a slope ranging from 0-40% which is found in soil type Inceptisols, distribution point Rafflesia found to be at a distance from the river between 250-400 meters, where the farther from the spring there Rafflesia are fewer. The results of model performance validation show that the habitat suitability model Rafflesia in the Maninjau Nature Reserve is included in the very good category (AUC = 0.982).